Limits to lifespan growth - Marta Gonçalves; Byung Mook Weon (Frontiers Media S.A., 2023)
A long-standing human lifespan debate is revival, and the consensus is yet to come on whether the maximum human lifespan is reaching a limit or not. This study discusses how mathematical constraints inherent in survival curves indicate a limit on maximum lifespans, implying that humans would have inevitable limits to lifespan growth.